DAYA SIMPAN SIRUP APEL HIJAU (Pyrus malus) DENGAN VARIASI GULA - Maimunah, Siti; Nurbaya, Siti; Zuhairiah, Zuhairiah (Jurnal Farmanesia, 2019)
Green apple syrup (Pyrus malus) has a shelf life that is influenced by the amount of added sugar because sugar given to a product with high levels can increase high osmotic pressure so that it can prevent microbial growth so that the material will be durable. This study aims to determine the taste, aroma, pH, color, and presence of fungi in green apple syrup (Pyrus malus) with the addition of sugar 40%, 50%, 60%, and 70% and the effect of adding sugar concentration 40%, 50%, 60%, and 70% to the resistance of green apple syrup (Pyrus malus). The type of research used is experimental research. The sample used was green apple (Pyrus malus) with a variation of sugar 40%, 50%, 60%, and 70% with the addition of citric acid to prevent the browning reaction. The results showed that sugar concentrations of 40% and 70% had a good shelf life for 28 days and green apple syrup (Pyrus malus) with sugar concentrations of 50% and 60% had a shelf life of green apple syrup (Pyrus malus) for 10 days with the moldy condition.